Techno-Economic Analysis of a Grid-Connected Hybrid System in Portugal Island - Bhattacharjee, Somudeep; Das, Rupan; Deb, Gagari; Thakur, Brahma Nand (International Journal of Computer Sciences and Engineering, 2019)
The present scenario describes that there are some untouched areas in the world, which are electrified but from pollution-generating energy sources. Since pollution generating energy sources provide the advantage of continuity of power supply so they are used especially in different islands of the world as compared to individual renewable energy sources. Most of these islands have huge possibilities for renewable power generation. Thus renewable energy based hybrid system is the only option that can replace these pollution generating energy sources. A hybrid system uses multiple energy sources for generating electricity due to which it helps in maintaining the continuity of power supply. However, the most significant thing is that the system should be cost-effectively attractive. In this paper, the optimization study of the hybrid system is done using the HOMER Pro software. This work investigates an optimum combination of grid-connected solar, wind and bio-generator based hybrid system, which can supply electricity in Portugal Island at an affordable price with an acceptable level of reliability. The main objective of the present study is to utilize the available solar, wind and biomass resources at the selected location to meet the demands of residential load, telecom tower load and water pump load in Portugal Island. The result of the study indicates that the system is a cost-effective system as well as it successfully satisfies the load demand by generating a large amount of energy every year.